Flexural Response of Continuous Concrete Beams Prestressed with External Tendons - Lou, Tiejiong (2013)
This article presents the results of a numerical investigation of the flexural behavior of continuous externally prestressed concrete beams. Aspects of behavior studied include the increase in stress in external tendons, moment redistribution in the post-elastic range and secondary moments due to prestressing. A finite element model for the full-range analysis of continuous externally prestressed concrete beams is introduced. The model predictions agree well with the experimental results. The analysis shows that the ultimate stress increase in external tendons of continuous beams is dependent on both the number and rotation of plastic hinges that can be developed at failure load. The degree of moment redistribution is significantly influenced by the nonprestressed tension steel and the pattern of loading. An approach based on linear transformation concept is designed to examine the secondary moments over entire loading up to the ultimate. The results indicate that the secondary moments increase linearly with the prestressing force and can be conveniently calculated by an elastic analysis.